Design of modern fine arts museum in Tondano - Fitri Fauziah Damayanti; Ferdinan S. R. P. Terok; Debbie Augustien Jeannet Harimu (Jurnal Arsitektur Archicentre, 2023)
The design of the Museum of Modern Fine Arts is a place for artists to exhibit their works, because museums in North Sulawesi Province do not allow them to accept collections of modern art due to differences in museum classification, and there is no museum with the classification of art museums in North Sulawesi Province. The design theme for this design is Expressionism Architecture with the concept of Focus On Material. This design makes those who previously did not understand and have no interest in fine art develop a curiosity about something that is seen and become an attraction for the general public to visit. The design method used is the Five Step Design Process Method taken from the book "Introduction to Architecture" by James C. Snyder and Anthony J. Catanese (1985), where at the design stage it is arranged systematically and is commonplace to do and is suitable for students who are in the learning process. The stages are initiation, preparation, submission of proposals, assessment, and action. The result of this design is the application of the Expressionism Architecture theme with the concept of Focus On Material in the form of building masses that follow the shape of the site location, showing (exposure) the natural color of the building materials used, using monochrome colors, using glass material so that the building gets natural lighting, using an open circulation pattern in the exhibition space so that visitors can see the entire room directly, as well as in rooms where acoustics need to be considered, materials that can reflect sound and materials that absorb sound are used.